Stress and Change in the Military Profession Attitudes of Officer Students at the South African Military Academy - Heinecken, Lindy (Scientia Militaria - South African Journal of Military Studies, 2012)
In this paper it is illustrated that there is a decline in the commitment to altruistic values if one analyses the survey data of junior officers among all four arms of service at the South African Military Academy. The results show a clear drift towards occupationalism as outlined by Moskos (1977) if the reasons for joining, preferred job characteristics, commitment to selfless service and the need for a representative association are analysed. This trend towards occupationalism could be ascribed to the decline in status and relevance of the armed forces in society, coupled to organisational change, which in placing the military profession under considerable stress in this current period of transition. Some implications of these trends for the military profession are discussed.